Molecular engineering and plant expression of an immunoglobulin heavy chain scaffold for delivery of a dengue vaccine candidate. Issue 12 (15th July 2017) - Kim, Mi‐Young; Van Dolleweerd, Craig; Copland, Alastair; Paul, Matthew John; Hofmann, Sven; Webster, Gina R.; Julik, Emily; Ceballos‐Olvera, Ivonne; Reyes‐del Valle, Jorge; Yang, Moon‐Sik; Jang, Yong‐Suk; Reljic, Rajko; et al.
Summary: In order to enhance vaccine uptake by the immune cells in vivo, molecular engineering approach was employed to construct a polymeric immunoglobulin G scaffold (PIGS) that incorporates multiple copies of an antigen and targets the Fc gamma receptors on antigen‐presenting cells. These self‐adjuvanting immunogens were tested in the context of dengue infection, for which there is currently no globally licensed vaccine yet. Thus, the consensus domain III sequence (cEDIII) of dengue glycoprotein E was incorporated into PIGS and expressed in both tobacco plants and Chinese Ovary Hamster cells. Purified mouse and human cEDIII‐PIGS were fractionated by HPLC into low and high molecular weight forms, corresponding to monomers, dimers and polymers. cEDIII‐PIGS were shown to retain important Fc receptor functions associated with immunoglobulins, including binding to C1q component of the complement and the low affinity Fcγ receptor II, as well as to macrophage cells in vitro . These molecules were shown to be immunogenic in mice, with or without an adjuvant, inducing a high level IgG antibody response which showed a neutralizing potential against the dengue virus serotype 2. The cEDIII‐PIGS also induced a significant cellular immune response, IFN‐γ production and polyfunctional T cells in both the CD4 + and CD8 + compartments. This proof‐of‐principle study shows that the potent antibody Fc‐mediated cellular functions can be harnessed to improve vaccine design, underscoring the potential of this technology to induce and modulate a broad‐ranging immune response.